2002
DOI: 10.1093/brain/awf211
|View full text |Cite
|
Sign up to set email alerts
|

Spatial neglect in near and far space investigated by repetitive transcranial magnetic stimulation

Abstract: Localized repetitive transcranial magnetic stimulation was used to disrupt visuospatial perception in the near and far space of six healthy volunteer subjects. In addition to the baseline condition, they were stimulated over the right posterior parietal cortex, the right or left dorsal occipital cortex or the right ventral occipital cortex, during the brief presentation of a transected horizontal line. Subjects had to indicate whether the part of the line to the left or right of the transection appeared longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
159
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(187 citation statements)
references
References 52 publications
23
159
2
Order By: Relevance
“…The role of rPPC in processing near space is in accordance with previous research (Bjoertomt et al, 2002;Halligan & Marshall, 1991;Lane et al, 2013;Mennemeier et al, 1992;Weiss et al, 2000), as is its relationship with egocentric processing (Committeri et al, 2004;Galati et al, 2000;Hillis et al, 2005;Medina et al, 2009;Neggers et al, 2006;Vallar et al, 1999). Neuropsychological research has indicated that the right hemisphere is involved in egocentric processing in near space (Iachini, Ruggiero, Conson & Trojano, 2013), although this finding was based on extensive fronto-parietal lesions in only four patients making it difficult to determine the precise brain area underlying their impairment .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The role of rPPC in processing near space is in accordance with previous research (Bjoertomt et al, 2002;Halligan & Marshall, 1991;Lane et al, 2013;Mennemeier et al, 1992;Weiss et al, 2000), as is its relationship with egocentric processing (Committeri et al, 2004;Galati et al, 2000;Hillis et al, 2005;Medina et al, 2009;Neggers et al, 2006;Vallar et al, 1999). Neuropsychological research has indicated that the right hemisphere is involved in egocentric processing in near space (Iachini, Ruggiero, Conson & Trojano, 2013), although this finding was based on extensive fronto-parietal lesions in only four patients making it difficult to determine the precise brain area underlying their impairment .…”
Section: Discussionsupporting
confidence: 88%
“…The chosen site was the intersection of the precentral and superior frontal sulci, a location that has repeatedly been used with TMS and confirmed as a functional locus (Grosbras and Paus, 2002;Paus, 1996;Ro et al, 1999). The rVO site was determined using the averaged scalp co-ordinates reported by Bjoertomt et al (2002), who also used this same site to examine near and far space processing.…”
Section: Transcranial Magnetic Stimulation and Site Localisationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast the involvement of the dorsal stream is based on its established visuo-spatial specialisation (Avidan et al, 2003;Ellison et al, 2003;Bjoertomt et al, 2002). Corthout et al, (2007) have recently delineated the arrival time of visual information in extra-striate visual cortex, whether feed-forward or feed-back, as between 50 and 100ms.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, neuropsychology and neuroimaging have identified many areas of specialisation interacting in broad streams of processing in these domains. However, our aim is to investigate the differential involvement of two areas in these three tasks: right lateral-occipital area (LO) known to be an important region in object recognition in the ventral stream (Ferber et al, 2005, Avidan et al, 2003, Lerner et al, 2002Kourtzi & Kanwisher, 2001) and an area of right posterior parietal cortex (PPC) known from many studies to have visuospatial specialisation (Avidan at al., 2003, Ellison et al, 2003Bjoertomt et al, 2002). As these areas are part of the established processing streams, if either is involved in the processing of a task, a deficit in performance should be demonstrated following disruption by TMS.…”
Section: Introductionmentioning
confidence: 99%